2002
DOI: 10.1086/340496
|View full text |Cite
|
Sign up to set email alerts
|

Optical and Infrared Observations of the Supernova SN 1999el

Abstract: Optical and near-infrared light curves of the Type IIn supernova 1999el in NGC 6951 are presented. A period of 220 days (416 days in the near-infrared) is covered from the first observation obtained a few days before maximum light. Spectroscopic observations are also discussed. Using as a distance calibrator the Type Ia SN 2000E, which occurred some months later in the same galaxy, and fitting a blackbody law to the photometric data we obtain a maximum bolometric luminosity for SN 1999el of ∼ 10 44 erg s −1 . … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
48
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 31 publications
5
48
0
Order By: Relevance
“…This behavior in the NIR colors during the rebrightening is not only totally at odds with that of other nonstellar objects, like SNe Ia (e.g., Valentini et al 2003), where dust is expected to play quite a marginal role in the light emission, but also different from, e.g., that of a ''dusty'' CC SN like the Type IIn SN 1999el (Di Carlo et al 2002). In the latter case, dust is expected to be the main cause of the observed NIR excess, and, in fact, the NIR colors evolve below the reddening band of the stellar main sequence in an (H À K) versus (J À H) diagram.…”
Section: Nir Color Evolutionmentioning
confidence: 61%
See 2 more Smart Citations
“…This behavior in the NIR colors during the rebrightening is not only totally at odds with that of other nonstellar objects, like SNe Ia (e.g., Valentini et al 2003), where dust is expected to play quite a marginal role in the light emission, but also different from, e.g., that of a ''dusty'' CC SN like the Type IIn SN 1999el (Di Carlo et al 2002). In the latter case, dust is expected to be the main cause of the observed NIR excess, and, in fact, the NIR colors evolve below the reddening band of the stellar main sequence in an (H À K) versus (J À H) diagram.…”
Section: Nir Color Evolutionmentioning
confidence: 61%
“…A number of frames were acquired at twilight and used to obtain normalized flat-field images using the differential flat technique, as described in Di Carlo et al (2002). Each sky-subtracted image was flat-field divided accordingly.…”
Section: Observations and Data Reductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These LEs may influence the spectra as well as the light curves of the sources when unresolved, in particular for events like Type II SNe that are likely located in dustrich environments (e.g. Schaefer 1987b;Chugai 1992;Di Carlo et al 2002;Otsuka et al 2012), but they have also been observed for SN 199T (Schmidt et al 1994), a SN Ia that is not necessarily expected to be in such a dust-rich environment. Roscherr & Schaefer (2000) found that LEs cannot explain the extremely long decline of SN IIn like SN 1988Z andSN 1997ab. The suggestion that historical SNe might be studied by their scattered LEs was first made by Zwicky (1940).…”
Section: Finding Lesmentioning
confidence: 99%
“…The spectra and light curves are based on SN 1999el (Di Carlo et al 2002), whereas the absolute B peak magnitude and scatter are obtained from Richardson et al (2002). After compensating for the different cosmological parameters, the resulting peak magnitude is −18.82.…”
Section: Type Iin Supernovaementioning
confidence: 99%